(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the modern era of internationalism, democratization and economic globalization the comparative public law received considerable importance and acceptance. The relations between individuals and the state are studied under the domain of public law. Therefore, the domain of law intensively focused on comparing the individual state relationships of various countries with the individual state relationships of the states of India is known as comparative public law. India is among those country which legal system has changed several times since it acquired a wisdom of improvisational legislation with a more individualistic approach. The in-depth knowledge of comparative public law enables to reader of this article to understand the subject particularly legal system in the wider socio-political. Presently, the significance of comparative public law has received the great interest of researchers across the globe due to the gradual raise in globalization where legal things, authority structures including the legal concepts migrate. Therefore, the present research article is primary attempt towards to analyze the role and significance of comparative public law. Further, this article provides insight into the key problems, methods involve, shortcomings associated with the comparative public law.